Decline of childhood overweight and obesity in Italy from 2008 to 2016: results from 5 rounds of the population-based surveillance system - Laura Lauria; Angela Spinelli; Marta Buoncristiano; Paola Nardone (BMC, 2019)
Abstract Background Given the effects of childhood obesity on future health, and the lack of information of its prevalence in Italy, a national surveillance system was implemented in 2007. It is OKkio alla SALUTE, part of the WHO/Europe Childhood Obesity Surveillance Initiative (COSI). This study reports the 2008-2016 trends by sex, area of residence and socio-demographic characteristics in the prevalence of overweight and obesity in primary school children (8-9 years). Methods In each round of the surveillance held in 2008, 2010, 2012, 2014 and 2016, a nationally representative sample of about 45,000 children, was weighed and measured with standard equipment and methods by trained personnel. Children were classified as normal weight, overweight or obese using World Obesity Federation (WOF) (formerly the International Obesity Task Force (IOTF)) and WHO cut-offs. Children's sex, area of residence and mothers' education and citizenship, were obtained using self-reported questionnaires and were assessed using multivariate logistic regression models. Results Between 2008 and 2016, the overall prevalence of obesity dropped from 12.0 to 9.3% (WOF-IOTF) and from 21.2 to 17.0% (WHO), while the overall prevalence of overweight (including obesity) from 35.2 to 30.6% (WOF-IOTF) and from 44.4 to 39.4% (WHO). Reduction in the prevalence of overweight and obesity was greater in boys (− 14.5%, p for trend< 0.001; and − 24.7%, p = 0.001) compared to girls (− 11.1%, p < 0.001; and − 19.2%, p = 0.034). Decreasing trends were observed in overweight prevalences within children resident in the center and in the south. Decreasing trends in obesity prevalences were observed among boys resident in the north and in the south, and among girls resident in the center. Decreasing trends were observed in overweight prevalences within socio-demographic characteristics, except among children with low educated and foreign mothers; and in obesity prevalences for children with medium educated mothers, and girls with Italian mothers. Conclusions From 2008 to 2016 a decrease of childhood overweight and obesity was observed in Italy. However, as these prevalences are still among the highest in Europe, there is need to continue their monitoring and implement more interventions to promote healthy lifestyles. More effort should be focused on children belonging to low social classes.